Multi-objective integer linear programming problems withFuzzy parameters in the constraint - Khaled Elsharkawy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we focus on the solution of multi-objective integer linear programming problems with fuzzy parameters (FMOILP). The fuzzy parameters are involved in the constraints, a-Pareto optimality is introduced, in addition a solution algorithm is described to solve the FMOILP and a parametric study is carried out on it, finally a numerical example illustrates various aspects of the results developed in this paper.